2016
DOI: 10.3329/pulse.v8i1.28095
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Cerebellopontine Angle Tumors in 34 Cases

Abstract: Introduction: Cerebellopontine angle tumors are a surgical challenge to many neurosurgeons who want to operate in this space. Although most of these tumors are benign, they are a challenge because of the complex anatomy and important neurovascular structures that traverse this space. Most common cerebellopontine angle tumor is vestibular schwannoma. The management of these cases is essentially surgical. There has been a change in the surgical strategy over the years from simple intratumoral decompression to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…However, in a study by Joarder et al facial nerve preservation was 74% for the large size tumors and 62% for giant tumors, which is comparable to our results. 16 In our case series, 16% of patients had a physiological injury to caudal cranial nerves (9,10,11,12) for which post-operative tracheostomy and PEG were done for 4 -6 weeks. This again emphasizes the fact that large and giant tumors have greater involvement of the nerves as compared to small tumors.…”
Section: Discussionmentioning
confidence: 82%
“…However, in a study by Joarder et al facial nerve preservation was 74% for the large size tumors and 62% for giant tumors, which is comparable to our results. 16 In our case series, 16% of patients had a physiological injury to caudal cranial nerves (9,10,11,12) for which post-operative tracheostomy and PEG were done for 4 -6 weeks. This again emphasizes the fact that large and giant tumors have greater involvement of the nerves as compared to small tumors.…”
Section: Discussionmentioning
confidence: 82%
“…Tumor size was not controlled for tumor type comparisons. Joarder et al reported on hearing outcome for 34 CPA tumors (27 VSs, 6 meningiomas, and 1 epidermoid) 6 . Hearing preservation was attempted in three VS and two meningioma cases.…”
Section: Discussionmentioning
confidence: 99%
“…While both tumor types share common presentation symptoms and intervention approaches, there are few studies that have directly compared hearing outcome after surgical resection for similarly sized tumors. 5,6 From a pathogenesis standpoint, the tumor originating cell-type differs between VS and meningioma suggesting that hearing outcomes may be different between the two. Schwann cells that envelope audiovestibular nerve fibers give rise to VS, 7,8 whereas arachnoid cap cells that surround the brain and spinal cord give rise to meningioma.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations